Benzoxazole derivatives as phototriggers for the release of butyric acid - Soares, Ana Maria Silva (2015)
With the aim of evaluating the application of new benzoxazole derivatives as photoactive moiety in butyric acid prodrugs, ester conjugates were synthesized by reaction of the chloromethylated heterocyclic precursors with the model drug. Photocleavage studies of the conjugates in methanol/HEPES buffer (80:20) solutions at different wavelengths of irradiation (254, 300 and 350 nm) confirmed the quantitative release of the butyric acid in short irradiation times.